Global Journalism: Main Aspects of Conceptualization - Kurysheva, Yulia Vladimirovna; Puiy, Anatoli Stepanovich; Litvinenko, Anna Alexandrovna; Bykov, Aleksei Yuryevich; Danilova, Iuliia Sokratovna (International Review of Management and Marketing, 2015)
Globalization processes and development of ICT have led to fundamental changes in understanding of journalism as a social process. The concept of global journalism needs conceptualization, as at the present stage the practice of professional activities is isolated from the theoretical framework. This article analyzes the main scientific approaches to the study of globalization processes in journalism and structures the main aspects of conceptualization of understanding the global journalism. Their basic theoretical and empirical evidence and refutation are formulated. Keywords: global journalism, global discourse, transnational information space JEL Classifications: D83; O3; O32; O33; Z13